Analisis Penerapan Kecerdasan Buatan (Artificial Intelligence) untuk Meningkatkan Keamanan Finansial Nasabah pada Sektor Perbankan - listyono, rizki; Titi Rapini; Umi Farida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The use of artificial intelligence (AI) in banking has grown rapidly in recent years, providing opportunities and challenges in dealing with it. AI in the banking world is expected to facilitate use, strengthen customer data security, and optimize risk management. This article aims to analyze the level of customer user experience towards banking services by utilizing artificial intelligence (AI). The analysis technique used in this study is descriptive with a quantitative approach, involving 100 respondents of various ages, various jobs and various educational backgrounds. The main requirement for respondents is that they are customers of various conventional banks in Ponorogo Regency who have used artificial intelligence (AI)-based banking services. Data were collected through questionnaires supplemented with secondary data in the form of documents related to the implementation of artificial intelligence in the banking service system. The application of AI in the banking sector is the detection and prevention of fraudulent transactions in real time, identity verification through biometrics, identity verification through biometrics, chatbots and virtual assistants for customer service, detecting suspicious activity, and the use of smart wallets. The findings in this study explain that artificial intelligence (AI) is able to increase the efficiency of services to customers, provide a better experience, and improve the quality of banking services. Customers are greatly helped by the use of artificial intelligence (AI)